2006
DOI: 10.1002/j.0022-0337.2006.70.4.tb04098.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Children: An Overview

Abstract: Hypertension in children is an increasing concern for health care professionals. Updated guidelines for the treatment of hypertension in children and adolescents were published in 2004. This report reviews the epidemiology and management of pediatric hypertension and suggests an oral health protocol to apply to hypertensive children in the dental setting. A web search was performed using Medline, PubMed, ISI Citation Index, and Cochrane evidence-based databases for articles regarding hypertension in children p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…TFF1 is a peptide that is expressed at low levels in normal breast tissue, [ 25 27 ] but at high levels in ERα + breast carcinomas [ 28 ] in response to E2 [ 29 ]. Since TFF1 is strictly controlled by the E2/ERα complex, it provides a good measure of estrogen signaling in breast cancer cells and a preliminary clinical study reported a parallel relationship between the TFF1 high expression levels and the proliferation of breast cancer cells [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…TFF1 is a peptide that is expressed at low levels in normal breast tissue, [ 25 27 ] but at high levels in ERα + breast carcinomas [ 28 ] in response to E2 [ 29 ]. Since TFF1 is strictly controlled by the E2/ERα complex, it provides a good measure of estrogen signaling in breast cancer cells and a preliminary clinical study reported a parallel relationship between the TFF1 high expression levels and the proliferation of breast cancer cells [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of hypertension in children the prevalence of obesity. 3 Recent studies in children and adults have showed that waist circumference is a more powerful risk factor for cardiovascular disorders than body mass index (BMI). 3,4 The increasing prevalence of obesity and hypertension indicates for children and adolescents for purposes of early intervention.…”
mentioning
confidence: 99%